2009
DOI: 10.1016/j.ydbio.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

dlx3b/4b are required for the formation of the preplacodal region and otic placode through local modulation of BMP activity

Abstract: The vertebrate inner ear arises from the otic placode, a transient thickening of ectodermal epithelium adjacent to neural crest domains in the presumptive head. During late gastrulation, cells fated to comprise the inner ear are part of a domain in cranial ectoderm that contain precursors of all sensory placodes, termed the preplacodal region (PPR). The combination of low levels of BMP activity coupled with high levels of FGF signaling are required to establish the PPR through induction of members of the six/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 87 publications
5
62
1
1
Order By: Relevance
“…Specification of the PPE necessitates complete inhibition of BMP activity after gastrulation (Kwon et al, 2010). This inhibition of BMP signalling has previously been postulated to be mediated by an antagonistic role of Cvl2 on BMP signalling (Esterberg and Fritz, 2009). That study suggested that the functionally redundant Distalless transcription factors Dlx3b and Dlx4b, which are PPE markers, activate the expression of cvl2 in the PPE.…”
Section: Temporal and Spatial Analysis Of The Formation Of Distinct Bmentioning
confidence: 93%
“…Specification of the PPE necessitates complete inhibition of BMP activity after gastrulation (Kwon et al, 2010). This inhibition of BMP signalling has previously been postulated to be mediated by an antagonistic role of Cvl2 on BMP signalling (Esterberg and Fritz, 2009). That study suggested that the functionally redundant Distalless transcription factors Dlx3b and Dlx4b, which are PPE markers, activate the expression of cvl2 in the PPE.…”
Section: Temporal and Spatial Analysis Of The Formation Of Distinct Bmentioning
confidence: 93%
“…Conserved signalling pathways control different cell behaviours according to elongation modes Despite these differences, there is an apparent conserved requirement for both FGF and Wnt signalling pathway components and downstream Cdx and Brachyury transcription factors for posterior body elongation across a range of vertebrates Esterberg and Fritz, 2009;Marlow et al, 2004;Row and Kimelman, 2009;Shimizu et al, 2005;Thorpe, 2005;Yang and Thorpe, 2011). Brachyury is also expressed in the tailbud during elongation in dogfish and lamprey embryos (Sauka-Spengler et al, 2003).…”
Section: Zebrafish Posterior Body Elongation Is Not Driven By Posterimentioning
confidence: 99%
“…Drosophila, zebrafish and mammalian Cv2 proteins can also inhibit signaling in some, but not all, in vitro assays (e.g. Binnerts et al, 2004;Esterberg and Fritz, 2009;Harada et al, 2008;Kelley et al, 2009;Moser et al, 2003;Serpe et al, 2008;.…”
Section: Context-dependent Effects On Bmp Signal Reception: Crossveinmentioning
confidence: 99%